#TITLE_ALTERNATIVE# - Edi Widodo NIM. 23595004, Catur
Abstract: A hardware description language has been constructed and its software interpreter has been built. This hardware description language is called D Language, and its interpreter isre called Silicon Interpreter D (SID). D Language is used to describe digital sequential circuit for synthesizing the circuit. By using D Language, the synthesis becomes relatively fast and easy. The steps of synthesis are making functional description, making state diagram, making hardware description language, and making logic gate description. A program in D Language is called a module. The module consists of an entity and architecture. An entity describes input port, memory, and output port. The architecture describes the behavior of an entity through changes of state from one state to another. SID is built to interpret D Language. The input of SID are the text of program written in D Language and data bits from a computer keyboard. The output of SID are data bits to a computer monitor. The input-output represent the the digital circuit behavior keyword : hardware description language, synthesis, interpreter.